Nucleotide receptor P2X7/STAT6 pathway regulates macrophage M2 polarization and its application in CAR-T immunotherapy - Qin Si; Lu Yang; Jie Liu; Hui Liu; Ruifang Bu; Na Cui (Immunobiology)
Background: A key factor underlying the failure of Chimeric Antigen Receptor-T Cell (CAR-T) therapy in ovarian cancer (OC) is the presence of an immunosuppressive tumor microenvironment, which is intricately linked to M2 polarization among tumor-infiltrating macrophages. P2X7 receptor has been previously documented as expressed within these macrophages and its correlation with M2 polarization is evident. This investigation scrutinizes whether silencing of P2X7 receptor within macrophages could lead to augmented anti-tumor potency of CAR-T. Method: Human peripheral blood mononuclear cells were artificially differentiated into macrophages or M2 macrophage in vitro. After silencing P2X7 receptor and/or overexpressing STAT6 within macrophages, the M1 and M2 markers were evaluated via flow cytometry, ELISA, and qRT-PCR. Additionally, the phosphorylation level of STAT6 was monitored by western blot. We engineered CAR-T cells targeting the non-functional P2X7 (nfP2X7) receptor, and co-cultured them with macrophages silencing P2X7 receptor along with OC cells. The anti-tumor effect of these CAR-T cells was assessed through evaluating OC cell viability, lactate dehydrogenase release, and IFN-γ levels. Result: P2X7 receptor silencing promotes M1 macrophage marker expression (CD86, TNF-α, IL-6, IL-1β), diminishes M2 macrophage marker expression (CD206 and IL-10) and suppresses STAT6 phosphorylation, whereas STAT6 overexpression reverses these phenomena. Furthermore, M2 macrophage suppresses the toxic effect of CAR-T cells on OC cells, while silencing the P2X7 receptor nullifies the immunosuppressive effect of M2 macrophages on CAR-T cells. Conclusion: Silencing P2X7 receptor can reverse M2 macrophage polarization by suppressing STAT6 activation, thereby enhancing the anti-tumor efficacy of CAR-T cells targeting nfP2X7 receptor in OC cell lines.